The Making of Korean Christianity : Protestant Encounters with Korean Religions, 1876-1915 - Oak, Sung-Deuk (Book collections on Project MUSE., 2013)
The surprising history of Korean evangelical Christianity. A major catalyst for the growth of Korean Christianity occurred at the turn of the twentieth century when Western missionaries encountered the religious landscape of Korea. These first-generation missionaries have been framed as destroyers of Korean religion and culture. Yet, as this book shows, existing Korean religious tradition also impacted the growth and character of evangelical Christianity. The melding of indigenous Korean religions and Christianity led to a highly localized Korean Christianity that flourished in the early modern era.